Outcomes and Costs of Patients Admitted to the ICU Due to Spontaneous Intracranial Hemorrhage. Issue 5 (May 2018) - Fernando, Shannon M.; Reardon, Peter M.; Dowlatshahi, Dar; English, Shane W.; Thavorn, Kednapa; Tanuseputro, Peter; Perry, Jeffrey J.; Rosenberg, Erin; Wijdicks, Eelco F.; Heyland, Daren K.; Kyeremanteng, Kwadwo
Abstract : Objectives: Spontaneous intracranial hemorrhage, including subarachnoid hemorrhage and intracerebral hemorrhage, is associated with significant morbidity and mortality. Although many of these patients will require ICU admission, little is known regarding their outcomes and the costs incurred. We evaluated this population in order to identify outcomes and cost patterns. Design: Retrospective cohort analysis of a health administrative database. Setting: Two ICUs within a single hospital system. Patients: Eight-thousand four-hundred forty-seven patients admitted to ICU from 2011 to 2014, of whom 332 had a diagnosis of spontaneous intracranial hemorrhage. Control patients were defined as randomly selected age, sex, and comorbidity index–matched nonintracranial hemorrhage ICU patients (1:4 matching ratio). Interventions: None. Measurements and Main Results: Mean age of ICU intracranial hemorrhage patients was 60.1 years, and 120 (36.1%) died prior to discharge. Intracranial hemorrhage was associated with a mean total cost of 75, 869, compared with 52, 471 in control patients ( p < 0.01). Mean cost per survivor of intracranial hemorrhage patients was 118, 813. Subarachnoid hemorrhage was associated with significantly higher mean total costs than intracerebral hemorrhage (92, 794 vs 53, 491; p < 0.01) and higher mean cost per day (4, 377 vs 3, 604; p < 0.01). Patients with intracranial hemorrhage who survived to hospital discharge were significantly costlier than decedents (100, 979 vs 30, 872; p < 0.01). Intracranial hemorrhage associated with oral anticoagulant use had a mean total cost of 152, 373, compared with 66, 548 in nonoral anticoagulant intracranial hemorrhage ( p < 0.01). Conclusions: Patients admitted to ICU with intracranial hemorrhage have high costs and high mortality, leading to elevated cost per survivor. Subarachnoid hemorrhage patients incur greater costs than intracerebral hemorrhage patients, and oral anticoagulant–associated intracerebral hemorrhage is particularly costly. Our findings provide novel information regarding financial impact of this common ICU population. Abstract : Supplemental Digital Content is available in the text.